2021
DOI: 10.1371/journal.pone.0256230
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic response to CPAP in obstructive sleep apnea versus COPD- obstructive sleep apnea overlap syndrome: Insights from a large national registry

Abstract: Background The symptomatic response to continuous positive airway pressure (CPAP) therapy in COPD-obstructive sleep apnea overlap syndrome (OVS) compared to OSA syndrome (OSA) alone has not been well studied so far. The aim of this study is to explore main differences in the clinical response to CPAP treatment in OVS compared to OSA alone. Study design and methods Using prospective data from the French National Sleep Apnea Registry, we conducted an observational study among 6320 patients with moderate-to-sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 31 publications
(39 reference statements)
1
22
0
Order By: Relevance
“…Another important finding from our study is that patients in the OVS group were more likely to have comorbidities like hypertension and cardiovascular disease. This finding aligns with prior research, which suggests that OVS patients experience a higher burden of comorbidities, particularly cardiovascular ones, compared to those with only OSA or COPD [55]. While the impact of OVS on cardiovascular outcomes varied across different studies and remains uncertain [9,16,38,42,43,53,61,62,[66][67][68][69][70][71][72][73][74][75][76][77][78], our study found that patients in the OVS group were linked to a 1.3-fold higher risk of developing hypertension and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Another important finding from our study is that patients in the OVS group were more likely to have comorbidities like hypertension and cardiovascular disease. This finding aligns with prior research, which suggests that OVS patients experience a higher burden of comorbidities, particularly cardiovascular ones, compared to those with only OSA or COPD [55]. While the impact of OVS on cardiovascular outcomes varied across different studies and remains uncertain [9,16,38,42,43,53,61,62,[66][67][68][69][70][71][72][73][74][75][76][77][78], our study found that patients in the OVS group were linked to a 1.3-fold higher risk of developing hypertension and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 90%
“…Available data indicate a higher prevalence of depression in OVS patients compared to those with pure COPD [52,53] but a similar prevalence compared to patients with OSA alone [9,42,54]. On the other hand, CPAP treatment has proven to be effective in reducing depression and enhancing the quality of life in individuals with OVS and OSA [55,56]. Therefore, it is crucial to promptly identify depression and provide appropriate treatment for patients with OVS, considering the potential negative impact of unrecognized and untreated depression on them, which can lead to increased fatigue and the greater utilization of healthcare resources [57][58][59].…”
Section: Discussionmentioning
confidence: 99%
“…Among OSA patients with available spirometry results, the coexistence of COPD was confirmed in 11.9-23.2% [33,44,47,48,62].…”
Section: Figurementioning
confidence: 88%
“…To align the process of OSA treatment, we developed the shared decision matrix. OSA treatment, for example, with PAP, improves a variety of daytime and sleep related symptoms irrespective of patients age and AHI at baseline [ 27 ]. This implicates a strong indication for treatment (moderate to very strong) in symptomatic OSA patients, in particular, as treatment options such as PAP and MAD are safe.…”
Section: Discussionmentioning
confidence: 99%